2011
DOI: 10.2202/1446-9022.1278
|View full text |Cite
|
Sign up to set email alerts
|

Strong Ties in a Small World

Abstract: Strong ties in a small world van der Leij, M.J.; Goyal, S. General rightsIt is not permitted to download or to forward/distribute the text or part of it without the consent of the author(s) and/or copyright holder(s), other than for strictly personal, individual use, unless the work is under an open content license (like Creative Commons). Disclaimer/Complaints regulationsIf you believe that digital publication of certain material infringes any of your rights or (privacy) interests, please let the Library kno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(18 citation statements)
references
References 47 publications
1
15
0
2
Order By: Relevance
“…Finally, the supply and technology category has 6 % individual authorships and five groups of two to 10 members. Previous studies have found that the productivity of a group is influenced by the number of its collaborators and that the most productive researchers, who have many interactions in their categories, are identified as experts in their area; this allows establishing new collaborations and an increase in their productivity (García, 2012;Hill, 2008;Hou et al, 2008;Leij & Goyal, 2011;Oh, Labianca, & Chung, 2006). This coincides with the results, since the forest management network, which is the largest, had more leaders and scientific production.…”
Section: Authorship By Networksupporting
confidence: 83%
See 3 more Smart Citations
“…Finally, the supply and technology category has 6 % individual authorships and five groups of two to 10 members. Previous studies have found that the productivity of a group is influenced by the number of its collaborators and that the most productive researchers, who have many interactions in their categories, are identified as experts in their area; this allows establishing new collaborations and an increase in their productivity (García, 2012;Hill, 2008;Hou et al, 2008;Leij & Goyal, 2011;Oh, Labianca, & Chung, 2006). This coincides with the results, since the forest management network, which is the largest, had more leaders and scientific production.…”
Section: Authorship By Networksupporting
confidence: 83%
“…These investments in strategic sectors seek an improvement in higher education and greater scientific production and international collaboration. In the current network of Mexican forest modelers, the 16 most productive and interrelated authors were identified ( Figure 5), according to the degree centrality of the nodes in each of the article categories (García, 2012;Hou, Kretschmer, & Liu, 2008;Leij & Goyal, 2011). These authors, due to having an advantageous position, are more likely to secure resources for projects, because they have more alternatives for collaboration with other researchers who also have significant networks (Hanneman & Riddle, 2005;Newman, 2004).…”
Section: Authorship By Networkmentioning
confidence: 99%
See 2 more Smart Citations
“…Other researchers [22], [23], have investigated a limited number of social network datasets, and found evidence that paths through these networks exist, traversing only 'strong ties', consistent with a model of overlapping community. However, the spread of contagions on such networks has not -to our knowledge -previously been examined in detail.…”
Section: A Other Relevant Literaturementioning
confidence: 72%